Antarctic Krill Protein Amyloid Fibrils as a Novel Iron Carrier for the Improvement of Iron Deficiency. - He, Xueqing; Lin, Songyi; Chen, Lei; Huang, Yihan; Hu, Jinhui; Sun, Na (Journal of Agricultural and Food Chemistry, 2025)
Iron fortification with food supplements remains the primary dietary strategy for improving iron deficiency anemia (IDA). This study used Antarctic krill protein for fibrillar design to form an Antarctic krill protein amyloid fibril (AKAF). The results indicated that peptides generated by proteolysis were a prerequisite for fibril assembly, forming elongated fibril structures and cross-linking upon heating. During this process, hydrogen bonds were rearranged, forming ordered β-sheet conformations (49.36 ± 0.21%); π-π stacking interactions among aromatic residues contributed to fibril formation. Further studies showed that AKAF effectively maintained iron in a bioavailable state and exhibited a high binding capacity (60.67 ± 0.69%). Moreover, the AKAF-iron complex markedly ameliorated hematological abnormalities in IDA mice, enhanced iron storage in the liver and spleen, and positively influenced the expression of iron homeostasis genes. This complex was also effective in alleviating gastric inflammatory responses induced by IDA. Overall, AKAF holds promise as an efficient iron delivery carrier.